The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m306933200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Rat Brain-specific Organic Anion Transporter (Oatp14) at the Blood-Brain Barrier

Abstract: ). Therefore, Oatp14 can mediate a bidirectional transport of T 4 . Sulfobromophthalein, taurocholate, and estrone sulfate were potent inhibitors for Oatp14, whereas digoxin, p-aminohippurate, or leukotriene C 4 , or organic cations such as tetraetheylammonium or cimetidine had no effect. The expression levels of Oatp14 mRNA and protein were up-and down-regulated under hypo-and hyperthyroid conditions, respectively. Therefore, it may be speculated that Oatp14 plays a role in maintaining the concentration of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
181
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(189 citation statements)
references
References 32 publications
7
181
0
1
Order By: Relevance
“…Oatp2 and oatp14 have been reported to be expressed in brain capillary endothelial cells (Gao et al 1999;Sugiyama et al 2003). Oatp3 and these transporters have similar substrate specificity, so that oatp2, 3 and 14 are likely to cooperate in BBB transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oatp2 and oatp14 have been reported to be expressed in brain capillary endothelial cells (Gao et al 1999;Sugiyama et al 2003). Oatp3 and these transporters have similar substrate specificity, so that oatp2, 3 and 14 are likely to cooperate in BBB transport.…”
Section: Discussionmentioning
confidence: 99%
“…Oatp2 and oatp14 are expressed at brain capillaries and choroid plexus, which form the blood-brain barrier (BBB) and the blood-cerebrospinal fluid barrier (BCSFB), respectively (Gao et al 1999;Sugiyama et al 2003). We have reported that oatp3 is localized at the rat choroid plexus (Ohtsuki et al 2003) and this finding raises the issue of whether oatp3 is expressed at the brain capillaries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, T4 can still enter the brain even in the absence of MCT8 suggesting that at least in mice another transporter must exist for mediating the uptake of T4 at the blood-brain barrier. A good candidate for this transit is Oatp1c1, a member of the organic anion transporting polypeptide family which not only exhibits a high degree of substrate specificity towards T4 (and the inactive metabolite rT3) but is also strongly expressed in capillary endothelial cells in the CNS (Sugiyama et al, 2003;Tohyama et al, 2004). Whether Oatpc1c1 is indeed the predominant T4 transporter at the blood-brain barrier can only by proven after the successful generation and characterization of a respective knockout mouse.…”
Section: Role Of Thyroid Hormone Transportersmentioning
confidence: 99%
“…Initial applications of the SSH methodology to the rat BBB led to the identification of a transcript, which encoded a protein with distant amino-acid homology to the organic anion transporting polypeptide type 2 (oatp2) (Li et al, 2001a(Li et al, , 2002. This orphan transporter was originally designated BBB-specific anion transporter type 1 (BSAT1) (Li et al, 2001a(Li et al, , 2002, and was subsequently shown to transport organic anions (Sugiyama et al, 2003), and was named oatp14, and finally designated Slco1c1 (Hagenbuch and Meier, 2003). Blood-brain barrier genomics investigations are viewed as a two-part process.…”
Section: Introductionmentioning
confidence: 99%